Meningkatkan Keaktifan Belajar Dan Bernalar Kritis Peserta Didik Pada Pembelajaran PAK Melalui Metode Discovery Learning - Misaya Misaya (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
Misaya, Improving Students' Active Learning and Critical Reasoning in PAK Learning Through the Discovery Learning Method. Accompanied by Jelahu Timotius and Wahyuningtiyas as Tutor. The purpose of this Classroom Action Research is to find out and measure whether or not the activeness of learning and Critical Reasoning of fifth grade students at SD Negeri 008 Jempang, West Kutai Regency, East Kalimantan Province has increased using the Discovery Learning Method. The research subjects were 8 students in class V SD Negeri 008 Jempang, consisting of 6 boys and 2 girls. The object of research is the active learning and critical reasoning of students in Catholic Religion and Ethics lessons on the material "I Was Created as a Man and a Woman". With data collection techniques are observation, documentation and tests. The results showed that there was an increase in the active learning and critical reasoning of Class V students on the material "I Was Created as a Boy and a Girl" by applying the Discovery Learning method. The increase in active learning and critical reasoning is evidenced by the average score of activity in cycle I which was 74.58 and in cycle II was 80.42, the score increased by 5.83 or an increase of 7.82%.